Studies of Heavy Metal Pollution in Water River Odra Estuary (North-West Poland) - Daniszewski, Piotr (Asian Journal of Chemistry, 2014)
The present research work deals with the quantification of toxic heavy metals in water samples collected from the lakes of river Odra estuary (North-West Poland). In present investigation, it was observed that the concentration range of cadmium was 0.41-0.59 ppm, chromium ranged 0.57-0.97 ppm, copper ranged 0.04-0.09 ppm, mercury ranged 0.03-0.09 ppm, nickel ranged 2.38-2.98 ppm, lead ranged 0.05-0.09 ppm and zinc ranged 2.65-3.96 ppm.